Perinatal asphyxia and hypothermic treatment from the endocrine perspective - Improda, Nicola; Capalbo, Donatella; Poloniato, Antonella; Garbetta, Gisella; Dituri, Francesco; Penta, Laura; Aversa, Tommaso; Sessa, Linda; Vierucci, Francesco; Cozzolino, Mariarosaria; Vigone, Maria Cristina; Tronconi, Giulia Maria; et al. (Frontiers in Endocrinology, 2023)
Introduction: Perinatal asphyxia is one of the three most important causes of neonatal mortality and morbidity. Therapeutic hypothermia represents the standard treatment for infants with moderate-severe perinatal asphyxia, resulting in reduction in the mortality and major neurodevelopmental disability. So far, data in the literature focusing on the endocrine aspects of both asphyxia and hypothermia treatment at birth are scanty, and many aspects are still debated. Aim of this narrative review is to summarize the current knowledge regarding the short- and long-term effects of perinatal asphyxia and of hypothermia treatment on the endocrine system, thus providing suggestions for improving the management of asphyxiated children. Results: Involvement of the endocrine system (especially glucose and electrolyte disturbances, adrenal hemorrhage, non-thyroidal illness syndrome) can occur in a variable percentage of subjects with perinatal asphyxia, potentially affecting mortality as well as neurological outcome. Hypothermia may also affect endocrine homeostasis, leading to a decreased incidence of hypocalcemia and an increased risk of dilutional hyponatremia and hypercalcemia. Conclusions: Metabolic abnormalities in the context of perinatal asphyxia are important modifiable factors that may be associated with a worse outcome. Therefore, clinicians should be aware of the possible occurrence of endocrine complication, in order to establish appropriate screening protocols and allow timely treatment.